On not researching school leadership: the contribution of S. J. Ball. (1st November 2013) - Gunter, Helen M.
Abstract : Stephen Ball's research continues to make a contribution to describing, understanding and explaining the political, social, economic and cultural context in which educational professionals locate their practices. Therefore, Ball engages with issues about school leadership, but he does not set out to present solutions for school leaders. Based on critical reading and interview data, I show how by not researching school leadership he makes a robust and relevant analysis of school leadership for the profession. He makes a contribution to understanding the realities of doing and thinking about leaders doing leadership and exercising leadership, where his starting point is to work with the profession as public intellectuals.